Review of equations for the calculation of Hydraulically Smooth Turbulent Flow in PVC pipes (2017)
PVC was incorporated as a pipe material in 1932 in Germany and in 1964 in the United States, and nowadays is widely used for the design of distribution networks. However, in the 19th and 20th century, materials with a higher roughness were more commonly used (such as concrete and lead) and with these materials were carried out the studies on which are based the most used design equations today. For this reason, the applicability of these equations is tested in the present article, using PVC as the material to verify. The tests were performed through measurements of pressure loss in different assemblies for extents of Reynolds numbers, in a range between 3x104 y 5x105 and relative roughness between 6x10-4 y 2x10-3. Based on the recommendations of common regulations in Colombia and the USA, this is the range where the design should be...